Uji antibakteri kombinasi ekstrak daun Biduri (Calotropis gigantea L.) dan daun Bandotan (ageratum conyzoides L.) - Munira Munira; Fina Rodisa; Muhammad Nasir (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Biduri leaves (Calotropis gigantea (L.) W.T. Aiton and Bandotan leaves (Ageratum conyzoides L.) are wild growing plants that are believed to be used as an antibacterial.Objectives: This research was conducted to determine the effect of combination ethanolic extract of Biduri and Bandotan leaves against Staphylococcus aureus and Staphylococcus epidermidis.Methods: This research is an experimental by using Completely Randomized Design (CRD) with 4 treatments which is P0 (aquadest), P1 (Biduri leaf extract), P2 (Bandotan leaf extract), and P3 (combination of Biduri and Bandotan leaf extract) with 5 replications. Microbiological test used was the diffusion method.Results: The results of Anova showed that combination of Biduri and Bandotan leaf extract very influential in the growth of Staphylococcus aureus dan Staphylococcus epidermidis. Duncan further test results showed that the largest average inhibition zone diameter in inhibiting Staphylococcus aureus was formed by P2 which is 14.14 mm, significantly different from P1 (9.46 mm) and P3 (11.20 mm), but P1 is not significantly different from P3. Toward Staphylococcus epidermidis, the largest average inhibition zone diameter also formed by P2 which is 17.06 mm that is also significantly different from P1 (10.14 mm) and P3 (12.66 mm), and P1 is not significantly different from P3.Conclusion: The combination of Biduri and Bandotan leaf extract very influential against Staphylococcus aureus and Staphylococcus epidermidis.